2006
DOI: 10.1128/aac.00342-06
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Reporter Cell Line for Detection of Infectious Varicella-Zoster Virus and Its Application to Antiviral Studies

Abstract: To simplify the titration of infectious varicella-zoster virus (VZV), we generated a reporter cell line that produced luciferase in a dose-dependent manner upon infection with cell-free VZV. A few VZV-infected cells were detectable by coculturing with the cell line. We demonstrated the usefulness of the cell line for antiviral studies.Varicella-zoster virus (VZV) causes varicella on primary infection and zoster upon reactivation. Both conditions may be associated with severe complications (1). For the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
1
20
1
1
Order By: Relevance
“…Transient-transfection experiments documented that the ORF10 promoter was strongly responsive to the major VZV immediate-early transactivator, IE62, as has been observed with many other VZV genes (43). Recently studies of several VZV promoters showed that their activities induced by VZV infection didn't differ from that mediated by IE62 alone, suggesting that the synergistic effects on the promoter activations induced by VZV infection could be reflected by IE62-mediating activation (49). There was little or no response to other known VZV transactivators, including IE4, the ORF61 protein, and IE63.…”
Section: Discussionmentioning
confidence: 75%
“…Transient-transfection experiments documented that the ORF10 promoter was strongly responsive to the major VZV immediate-early transactivator, IE62, as has been observed with many other VZV genes (43). Recently studies of several VZV promoters showed that their activities induced by VZV infection didn't differ from that mediated by IE62 alone, suggesting that the synergistic effects on the promoter activations induced by VZV infection could be reflected by IE62-mediating activation (49). There was little or no response to other known VZV transactivators, including IE4, the ORF61 protein, and IE63.…”
Section: Discussionmentioning
confidence: 75%
“…Similar cell lines have been described for several other viruses (34). We and others generated reporter cell lines for herpesviruses, including herpes simplex virus, B virus, HHV-8, and VZV (7,17,34,42,47). Two reporter cell lines for HCMV that depend on the activation of the UL54 (DNA polymerase) promoter were also published previously (13,45).…”
Section: Discussionmentioning
confidence: 99%
“…MeWo cells were used for infection with VZV (P-Oka). MV9G, a VZV reporter cell line, was used for titration of VZV (47). A telomeraseimmortalized human fibroblast cell line, hTERT-BJ1 (Invitrogen), was grown in Dulbecco's modified Eagle medium-medium 199 (4:1) supplemented with 10% FBS and infected with the HCMV Towne and RC256 (41) strains and with several HCMV clinical isolates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EC 50 s of 35B2 against several laboratory and clinical strains were determined by the focus reduction assay using cell-associated viruses as inocula, since most low-passage-number VZV strains are cell associated. It is well known that EC 50 s obtained by using cell-associated viruses as inocula are higher than those obtained by using cell-free viruses (44,57). Growth of ACV-resistant strains V-Oka-YSR and Kanno as well as other ACV-sensitive strains and clinical isolates was inhibited by the 35B2 treatment at similar concentrations ( Table 2).…”
Section: Identificationmentioning
confidence: 89%